2014
DOI: 10.1590/1678-41626120
|View full text |Cite
|
Sign up to set email alerts
|

Echobiometrics kidney and renal artery triplex doppler of canine fetuses

Abstract: The aim of this study was to assess the sogographic parameters and biometry of canine fetal kidneys using the B mode, and to determinate the vascular index of the fetal renal arteries using the Doppler Triplex. Twenty four Shi-tzu and Pug, weighting between 4 and 10 kg, aging between 4 and 6 years old were evaluated. The B mode, the fetal renal echobiometry and regularity of the renal surface, echotexture and cortex:medular ratio were evaluated during the 5th, 6th, 7th and 8th weeks of pregnancy. At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In human the of renal biometry is utilize as an additional method for estimation of fetal age and to identify congenital kidney diseases (Dias et al 2014). This parameter contradicts that reported by Feliciano et al (2014), who suggested kidney echobiometry as an appropriate predictor of gestational age in bitches.…”
Section: Discussionmentioning
confidence: 92%
“…In human the of renal biometry is utilize as an additional method for estimation of fetal age and to identify congenital kidney diseases (Dias et al 2014). This parameter contradicts that reported by Feliciano et al (2014), who suggested kidney echobiometry as an appropriate predictor of gestational age in bitches.…”
Section: Discussionmentioning
confidence: 92%
“…In canine fetuses, ultrasonographic kidney development and echobiometrical parameters were seen in healthy fetuses [12,17]. Canine fetal kidney echogenicity was qualitatively assessed and reported to be lower than the maternal kidney echogenicity from week 5 to 8 of pregnancy [33].…”
Section: Discussionmentioning
confidence: 99%
“…Initially at week 5 there is no diastolic flow in the foetal abdominal aorta but starting week 6, slow diastolic flow is noted (Umamageswari et al, 2018). The foetal renal arteries reveal increasing PSV and EDV and constant PI and RI from week 5 to 8 of pregnancy (Feliciano et al, 2014). The middle cerebral artery of the foetus reveals increases in PSV and EDV and decreases in PI and RI from the 5th to the 8th week of pregnancy (Feliciano et al, 2013).…”
Section: Doppler Ultrasonography Of Maternal and Foetal Blood Vesselsmentioning
confidence: 99%